Communication strategies used by Malaysia Ministry of Health in combating rumours on H1N1 pandemic / Wan Azfarozza Wan Athmar … [et al.] - Wan Athmar, Wan Azfarozza; Wan Faizal, Wan Nur Atiqah; Mohd Baharudin, Ain Nabilah; Ismail, Muhammad Affili; Mazlan, Nur Mazuina; Ruhaizat, Nor Shahira; Ali Kamsani, Mohd Kamal Hafeiz (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
The H1N1 pandemic has brought unprecedented panic all over the world and Malaysia is also affected by of this global health problem. In 2009, we witnessed 77 death tolls in Malaysia alone and we are warned of a second wave ofH1N 1. The aim of this research is to identify the communication strategies used to disseminate information about H1N1 outbreaks, actions taken to prevent rumours about H1N1 from spreading and the communication challenges faced by the corporate communication department of Malaysia’s Ministry of Health on H1N1 outbreaks. This study utilized the qualitative research approach which is in-depth interview. The research found that the Ministry of Health has utilized all communication tools to disseminate information on HINT and the communication strategies are based on culture, politics and economy aspects of this country. Frequent media monitoring, educating the public and transparency are actions taken to curb the rumours. The way audience perceived information on HINI, misinterpretation of the information and dealing with media from the private sectors are three major communication challenges faced by the Malaysia’s Ministry of Health